A reused roll or a ‘curious Christian codex’? Reconsidering British Library Papyrus 2053 (P.Oxy. 8.1075 + P.Oxy. 8.1079) - Charlesworth, Scott D. (Buried History: The Journal of the Australian Institute of Archaeology, 2018)
Recently, Brent Nongbri has proposed that British Library Papyrus 2053 came from a codex and not a roll. His primary concern is codicology and he pays no attention to scribal tendencies, including the implications of the palaeographical characteristics of the hand. In a careful reassessment that takes into consideration codicology, palaeography, scribal tendencies, and the physical condition of the papyrus itself, Nongbri’s argument is found to be flawed in a number of ways which speak directly to the possible origins of BL Pap. 2053. All indications are that a third-century Christian used the back of a roll containing Exodus to produce a copy of Revelation for ‘private’ use.